Hindu-Buddhist Historical Heritage Module as Material Alternative Teaching for Semarang Regency High School Students - Sulistiawan, Eko; Jayusman, Jayusman; Suharso, R (Universitas Negeri Semarang, 2022)
The purpose of this study was to analyze the need for developmental teaching materials and the influence of Hindu-Buddhism in Indonesia for Semarang District High School students, knowing the development of module teaching materials about the relics of Hindu-Buddhist history in Semarang Regency and to find out the feasibility of module teaching materials about the Hindu-Buddhist heritage in Semarang Regency that was developed. This research method uses research and development methods or Research and Development. The research and development phase is carried out to look for potential problems, data collection or information, product design, design validation, and design improvement. The results showed that historical learning in SMA 2 Ungaran used teaching materials in textbooks, student worksheets, and modules developed by teachers, while SMA Kanisius Bhakti Awam only used textbooks. All the teaching materials need to be more attractive design, and there are no local materials yet. 'The development of module teaching materials is done through several sound stages. The first stage material validation results got 73.3%, and the second stage validation got 82.63%. Stage I media validation yielded 68.5% results, and stage II validation received 89.5%. Meanwhile, the results of practitioner validation were 87.76%, and the results of student responses were 84.12%. So, the teaching materials on the relics of Hindu Buddhist history in Semarang Regency are excellent and appropriate for learning history.